West Cotton, Raunds A Study of Medieval Settlement Dynamics AD 450-1450. Excavation of a deserted medieval hamlet in Northamptonshire, 1985-89 - Chapman, Andy (Historic England, 2010)
The open area excavation of nearly a half of the small deserted medieval hamlet of West Cotton, Raunds, Northamptonshire has revealed the dynamic processes of constant development in a way that has rarely been achieved on other comparable sites in England. Its origins have been seen to lie in the mid tenth-century plantation of a planned settlement based on regular one-acre plots, which occurred within the political context of the reconquest of eastern England by the Saxon kings and the subsequent reorganisation of settlement and society within the Danelaw. The settlement contained a major holding comprising a timber hall with ancillary buildings and an adjacent watermill, with perhaps a second similar holding and dependent peasants nearby. It was established on the edge of the floodplain at the confluence of a tributary stream with the River Nene, on a major valley-bottom route way.